Modal Analysis of a DFIG-Based Wind Farm Interfaced With a Series Compensated Network - Fan, Lingling; Zhu, Chanxia; Miao, Zhixin; Hu, Minqiang (IEEE transactions on energy conversion, 2011)
Interests of subsynchronous resonance (SSR) in series compensated electric networks with wind power penetration have arisen recently. To better understand the nature of such systems, modal analysis of a doubly-fed induction generator (DFIG)-based wind energy system interconnected with a series compensated electric network is conducted in this paper. The system model is built in Matlab/Simulink. The major contributions of the paper include: 1) identification of the four system modes (SSR, supersynchronous, electromechanical, and shaft modes) of a DFIG-based wind farm interfaced with a series compensated network, 2) investigation of the impacts of various parameters and operating conditions on those modes, and 3) prediction of the dynamic performance of the system using modal analysis and confirmation of such prediction via time-domain simulation results.